Mass Inventiveness in USSR (1954–1990): An Evaluation of Effectiveness - D. A. Pinaeva (Научный диалог, 2024)
This article explores the historical development of the planning and incentive system for inventiveness and rationalization in the Soviet Union from 1954 to 1990. Through an analysis of published sources and archival materials, it concludes that during the studied period, quantitative metrics dominated the evaluation of inventiveness and rationalization effectiveness, expressed in absolute figures. Notably, the methodologies for calculating these metrics underwent several changes, complicating comparative assessments and the study of phenomena and processes over extended time frames. The development of mass inventiveness enabled the USSR to achieve a leading position globally in terms of the number of registered invention applications, with the cumulative economic impact of implemented rationalization proposals and inventions showing consistent growth throughout the period examined. However, it is noted that relative indicators reflecting the qualitative state of inventiveness and rationalization revealed low rates of sectoral development. The study concludes that qualitative measures of effectiveness did not play a decisive role in the planning, evaluation, and encouragement of inventiveness and rationalization in the USSR.